Effect of using smartphone before bedtime and sleep quality of middle-adulthood officers at Chulalongkorn University - Booranasuntikul, Bhakkhaphorn; Kanchanakhan, Naowarat (Chulalongkorn Medical Journal, 2021)
Background: Nowadays, smartphone has become part of everyday life of the people and tend to be more active continuously. However, it causes many adverse effects, both physically and mentally including potentially resulting in poor sleep quality. Objective: The aim of this study was to investigate the effect of using smartphone before bedtime and sleep quality among the middle-adulthood university officers at Chulalongkorn University. Methods: This cross-sectional descriptive study was conducted among middle-adulthood officers at Chulalongkorn University, aged between 45 - 64 years from 5 faculties within the university. The data were collected by using self-reported questionnaires including general characteristics and covariate factors, behavior of smartphone usage before bedtime, suanprung stress test-20 (SPST-20), and Thai version of Pittsburgh Sleep Quality Index (T-PSQI). The sleep quality was presented by number and percentage. The associated factors were analyzed by Chi-square test, Fisher’s exact test and the potential predictors of poor sleep quality were analyzed by multivariate logistic regression analysis. Results: There were 350 participants in this study, 56.0% of them were female with an average age of 49.5 2.9 years old: 23.1% of them had poor sleep quality. The associated factors of poor sleep quality were included male, age > 50 years, the using of psychological pills and sleeping medicine, the using of smartphone before bedtime, light adjustment when using smartphone in a dark room, and light adjustment when using smartphone before bedtime (P < 0.05). The predictors of poor sleep quality were gender, age, and light adjustment when using smartphone before bedtime (P < 0.05). Conclusion: Poor sleep quality problems can affect both physical health and work efficiency. Light adjustment when using a smartphone in a dark room and light adjustment when using a smartphone before bedtime has a significant correlation with sleep quality.